Synthesis of homogeneous protein-stabilized rutin nanodispersions by reversible assembly of soybean (Glycine max) seed ferritin. Issue 40 (7th May 2015) - Yang, Rui; Zhou, Zhongkai; Sun, Guoyu; Gao, Yunjing; Xu, Jingjing; Strappe, Padraig; Blanchard, Chris; Cheng, Yao; Ding, Xiaodong
<x xml:space="preserve">Abstract</x> We have studied the soybean seed ferritin stabilized rutin nanodispersions with improved water-solubility, thermal stability, and UV radiation stability.